2017
DOI: 10.5334/dsj-2017-016
|View full text |Cite
|
Sign up to set email alerts
|

Building a Disciplinary, World-Wide Data Infrastructure

Abstract: Sharing scientific data with the objective of making it discoverable, accessible, reusable, and interoperable requires work and presents challenges being faced at the disciplinary level to define in particular how the data should be formatted and described. This paper represents the Proceedings of a session held at SciDataCon 2016 (Denver, 12-13 September 2016). It explores the way a range of disciplines, namely materials science, crystallography, astronomy, earth sciences, humanities and linguistics, get orga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Funding agencies and academic institutions should also fund and maintain infrastructure for data sharing, including providing training and support for research-ers who intend to share data [8]. This is especially important for those disciplinary areas without cross-domain infra-structure or common practice [23].…”
Section: Discussion and Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Funding agencies and academic institutions should also fund and maintain infrastructure for data sharing, including providing training and support for research-ers who intend to share data [8]. This is especially important for those disciplinary areas without cross-domain infra-structure or common practice [23].…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…However, a study found that a key challenge for Humanities scholars is their lack of ability with tools and methods to link data housed in different archives [7]. A recent study also identified infrastructure issues as one of the main barriers for researchers in Humanities to share data because there is no single common practice across Humanities, thus calling for the development of cross-domain infrastructure components to allow data sharing among Humanities [23]. Ethical issues involve human subjects may affect academics’ willingness and ability to share research data.…”
Section: Background and Contextmentioning
confidence: 99%
“…Yet each provides a valuable service to science, and is highly regarded within the research community. This diverse and thriving ecosystem of databases, underpinned by data exchange standards and the desire to ensure the highest achievable quality, is key to the strength of crystallography's world-wide data infrastructure (Genova et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The way different disciplines organise themselves to tackle the development of their disciplinary interoperability framework was discussed during a session [24] of the SciDataCon 2016 Conference 12 , which was held in Denver (USA) on 2016, September 11 th − 13 th . The panel included representatives from humanities, linguistics, astronomy, earth sciences, material sciences and crystallography.…”
Section: Data As An Infrastructure: Examples From Different Disciplinesmentioning
confidence: 99%
“…As explained in [24], international organizations such as GEO, CODATA and the RDA can be used to help disciplines which are not strongly organised at the international level to discuss their data framework. International discussion forums can be established as CODATA Task Groups and/or RDA Interest and Working Groups (Section 5).…”
Section: Data As An Infrastructure: Examples From Different Disciplinesmentioning
confidence: 99%